Mathematical Creativity: A Systematic Review of Current Research on Eye-Tracking Technology - Farman; Siswono, Tatag Yuli Eko; Lukito, Agung; Dewi, Ratna Sari; Ndayizeye, Oscar; Hali, Fitriyani (Journal of Applied Science, Engineering, Technology, and Education, 2025)
Recent empirical research on mathematical creativity using eye-tracking (ET) technology has faced challenges in developing comprehensive overviews due to the diversity of tools, task types, ET metrics, and identification methods. Thus, this systematic review attempts to examine studies that focus on mathematical creativity and incorporate ET technology. Guided by Newman and Gough’s seven-step approach, a Scopus database search covering publications up to 2024 identified five eligible empirical studies collected for this study. The review reveals that researchers employed two primary types of eye trackers: screen-based trackers, which are affordable and unobtrusive, and eye-tracking glasses, which enable participants to engage in paper-and-pencil tasks while moving naturally. To stimulate creative thinking, the studies utilized open-ended mathematical tasks—particularly geometry-based multiple solution tasks (MST) and visual modeling tasks—that encourage divergent exploration. In analyzing creative processes, researchers combined ET metrics such as fixation duration, fixation count, and scan paths with gaze-overlaid videos, offering complementary insights into visual attention patterns and idea development. Additionally, several studies integrated ET with stimulated recall interviews (SRI), allowing participants to reflect on their strategies and deepening the interpretation of cognitive processes. This methodological combination effectively captures both visual behaviors and participants’ reflections, highlighting the complexity of creative thinking in mathematics and offering guidance for future research and instructional practice.